The Effect of Time Management, Organizational Support, and Family Support on the Work-Life Balance of Female Employees at the Babakan Health Center - Parju Sahril Wahid; Mukmin Suryatni (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to determine the influence of Time Management, Organizational Support, and Family Support on the Work-Life Balance of female employees at the Babakan Health Center. A type of causal associative research with a quantitative approach used Partial Least Square (PLS) analysis on 57 female employee respondents. The results showed that time management had no significant effect (p=0.507), organizational support had a significant positive effect (p=0.041), and family support had a significant positive effect (p=0.017), with an R-square of 0.65.